Kecenderungan Public Speaking Anxiety pada Mahasiswa - Elin Maulida Rahmawati; Rina Nurhudi Ramdhani; Agus Taufiq; S.A. Lily Nurillah (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2023)
The ability to speak in public is very important to be owned and mastered by students so as to produce the right graduate performance in the work environment. The reality on the ground turns out that not a few people are embarrassed to speak in public, causing inappropriate behavior such as experiencing symptoms of public speaking anxiety. This study aims to determine trends in anxiety about speaking in front of general students at the Indonesian University of Education Batch 2021. The research method used was a questionnaire in the form of a package arranged in the form of a Google Form. Data processing in this study used data analysis techniques in the form of descriptive statistical techniques to reveal the level of public speaking anxiety tendencies among students. The results of the descriptive statistical analysis regarding public speaking anxiety of Indonesian University of Education students Class of 2021 with an average score of 76.28 are in the interval 65.5 £ X < 87.1, which is in the medium category.